MAKEDONSKA EGZILANTSKA KNJIŽEVNOST - DIO INTERKULTURNE POVIJESTI KNJIŽEVNOSTI (Philological Studies, 2019)
The new Macedonian Literature was formed in the 19th century by writers in exile, widely understood as territorial, linguistic, ideological and existential dis- placement. Without their own state and the state’s apparatus which would defend the cultural heritage of the Macedonian People, without a literary practice in their own codified mother tongue as foundation of the national literature, without an organised and continuous literary life on their own soil and in front of their own literary au- dience, under constant pressure of being denied, attempts of being assimilated, they were alienated and isolated, moving over wider geographical areas of cultural pluralism and they were forced to accept the language of the new country with a wish to narrate and express their creativity, all in an attempt to witness the authentic existence of an autochthonous area. The Macedonian Literature in exile is founded on rich oral folk creations, myths and common cultural and historical memory of the Macedonian People who were forming their own cultural identity-although it was only symbolically and historically connected to its own territory. The Macedonian writers in exile were intermediaries between the cultures of the new country and the one of their roots. They are intermediaries between two or more national literatures on the Balkans, a wider pluralistic space in which cultures were interacting closely. The writers in exile were and are the most important factor in the inter-literary process, this being based on their multilingualism, multiliteracy; the territory they inhabit and in which they move; the function of their opus in two or more literary environments. But none of them have been able to avoid the herme- neutics of their own homeland, which brings to surface the complex and serious issues of origin, belonging, existential destiny, or their own emancipation from the previously framed homeland context.Instead of being a virtue, often their polyvalent identity becomes a curse. They manage to transform the pain (caused by the continuous state of non-belonging ) into a literary creation which might have not come to existence at all (if that pain was not there). Whatever is lost geographically, is being replaced culturally and literary. The lost homeland becomes a way of literary ex- pression and the lost feeling of belonging becomes a way of reclaiming the same.In the light of cultural studies, the exiled writers are on the social margins and are a literary phenomenon of their Athers. Literature is a vast space for discovering the Alter. In spite of this, and indeed because of this-the exiled Macedonian writers are assuring albeit atypical but continuous historical existence of the Macedonian Literature.